THE DEVELOPMENT OF SCIENCE MOBILE LEARNING WITH CONSERVATION VISION BASED ON ANDROID APP INVENTOR 2 - Taufiq, Muhamad; Amalia, Andin Vita; Parmin, Parmin (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Abstract ___________________________________________________________________ The purpose of this research was to develop science mobile learning conservation vission based on android app inventor well tested and find out the user response to the application of mobile learning science as supplement materials of learning mobile based. The methodology used in the making of this application is the waterfall methodology. Science mobile learning applications conservation vission is expected to help the students in particular and the scientific community in general to get the ease of learning science concepts using a Smartphone device without having to print using paper (paperless). Applications of science mobile learning include by supporting features of images, videos and quizzes. The conclusions in this research that has generated the application of science mobile learning conservation vision feasible to use to learn the concept of science and efforts to reduce the use of paper (paperless), application of science mobile learning get good response from the community of users related to accessibility, suitability of the features and content of science, and its utilization which supports reducing the use of paper.